Pemberdayaan Masyarakat Melalui Sosilaisasi Stunting Dan Kebersihan Lingkungan - Sudirman Sudirman; lexy Kareba; Jumain Jumain; Wahyu Wahyu; Agustinus Talindong; Saiful Ambodale (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Stunting remains a significant public health challenge in Indonesia, especially in rural areas with limited access to nutrition and sanitation. This community service activity aims to provide residents of Tosale Village, Donggala Regency, with knowledge about stunting prevention and the importance of environmental hygiene through a participatory educational approach. The implementation methods included field observations, stunting discussions, installation of educational visual media, as well as mutual cooperation activities and the cultivation of medicinal plants and vegetables. The results of the activity showed an increase in community understanding of balanced nutrition, clean and healthy lifestyles, the cultivation of medicinal plants and vegetables, and the revival of a culture of mutual cooperation. The stunting discussion forum served as a platform to encourage cross-community participation in the village, while visual media strengthened health literacy through easily understandable messages. Overall, this activity demonstrated that a participatory approach can increase collective awareness and preventive behavior against stunting while strengthening the independence of village communities in creating a sustainable healthy environment.